The Experience and Meaning of Mind Happiness Aging in the Buddhist context - Suknarin, Rassamee; Oppawongsapat, Dhammawat; Rudtanasudjatum, Koolarb; Choaniyom, Wanassara; Okamura, Hiroshi (Journal of International Buddhist Studies, 2017)
The purpose of this qualitative research was to study the meaning and experiences of mind happiness aging in Buddhist contexts. Data were collected by conducting in-depth interview with 15 elders who had mind happiness and were recruited through a purposive sampling together with a snowball selection. Data were analyzed through a content analysis and validated by member checking and peer debriefing. Study results revealed that mind happiness aging in Buddhist contexts referred to a purely clear and peaceful feeling free from any pressures that was generated from inside and was resulted from leading a virtuous life in favor of the benefits for oneself and others; and from attaining wisdom to recognize the world in line with reality. This meaning covered the 4 main components: 1) Having faith in virtue; 2) Employing virtue as the basis for leading one’s life; 3) Living with others in a sharing and caring manner; and 4) Attaining wisdom to have insight into all beings in accordance with actuality. This study has come up with a number of evidence-based findings that are comprehensively in line with the happiness defined in the contexts of Buddhist principles, which is categorized into several levels ranging from the happiness in the level that a person is dependent on consumable objects (but only up to a necessary level for fulfilling the needs of humans) and the happiness that has been developed further to the ultimate one, which is attained from having insight wisdom to know and understand all beings in accordance with actuality, and from getting liberated from all defilements.